Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Jasa Service Komputer (Studi Kasus Metro Komputer Service Bandar Lampung) - Lusiana, Lisda; Gultom, Indriati Agustina (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to analyze customer satisfaction towards Metro Bandar Lampung Computer Services by considering key factors such as physical evidence, reliability, warranty, responsiveness, and empathy. The study involved 90 respondents who were part of Metro Computer Service's customer base. The main objective was to gain a deeper understanding of the ongoing dynamics at Metro Computer Services Bandar Lampung. The results of this study show how the five overall factors of customer satisfaction influence the level of customer satisfaction at Metro Computer Service Bandar Lampung.